Green Economic Potential Through the Halal Tourism Strategy in The City of a Thousand River: Green Economic Potential Through the Halal Tourism Strategy in The City of a Thousand River - Putra, Ananda Aulia; misrah, Misrah (UMBanjarmasin, 2022)
The green economy is an environmentally friendly space concept with the development of innovation and creativity which is utilized and managed so that the earth and its contents achieve prosperity and prosperity for mankind for future generations. Activities in the economic sector should make use of the green economy for friendly energy sources. environment, which can prevent damage to ecosystems, and reduce carbon emissions. The implementation of a green economy can support a balance in each region that is able to increase natural resources, human resources, and the level of quality of life from finances in the area. Support for a green economy that can be implemented the local government has a vision and mission in equality that makes the dam prosperous, sustains a healthy environment and business opportunities that can open up many jobs for the wider community. Development of a green economy that can increase awareness to every individual to b Together with the urgency in the use and practice that continues to pay attention to aspects of the environment that are experiencing a decline in function, so is the importance of a green economy that is able to foster growth in the economic sector which is a pillar of the sustainability of each region and region in all countries both in the social sector which is able to increase intensity in sustainable natural resources and to protect the sustainability of human life and the environment in the future